The Classification of Characters' Emotions in the Novel Rumah Untuk Alie and the Lesson Plan - Mansyah, Dinanda Nour; Pramulia, Pana (Raja Zulkarnain Education Foundation, 2025)
This study aims to describe the characterization and classification of characters in the novel Rumah untuk Alie by Lenn Liu. In terms of process and results, this study uses a qualitative descriptive method. From the perspective of data sources, this study is a library research. Data were collected using observation guidelines for the novel Rumah Untuk Alie. Data were analyzed using a literary psychology approach, utilizing David Krech's theory of emotional classification, which Albertine Minderop has modified into three stages: data reduction, data presentation, and conclusion drawing. Data validity was obtained by theory triangulation. The results of the study on the classification of character emotions: 1) suppressed guilt occurs when the Jdoraksa family feels regret for their treatment of judging Alie; 2) Suppressed Guilt; 3) self-punishment is carried out by Alie who ends her life by consuming high doses of drugs and drowning her body in the sea; 4) shame appears when the video of Alie's fight with the Hexa Gang goes viral and the incident when Alie asks for a hug from Natta; 5) sadness comes when Gianla dies; 6) hatred is very dominant in the character of Alie, often experiencing physical violence from her family; 7) love comes from Alie's feelings of affection for her family and Selena's feelings of love who are always there when Alie needs them. The results of the prominent emotional classification of this study are hatred, while the results of the weak emotional classification are the concept of guilt. The results of the prominent emotional classification of this study are hatred, while the results of the weak emotional classification are the concept of guilt.